Estabilidade de membrana de eritrócitos em portadores de depressão - Netto, Rita de Cássia Mascarenhas (2009)
Depression in the elderly has been presented as a neurodegenerative condition associated with increased age, deficiencies of folate and/or cobalamin, elevated serum levels of homocysteine and changes in the composition and behavior of biological membranes. Aiming to test the validity of the relationships between depression, aging, general malnutrition, folate and cobalamin deficiencies, homocysteinemia and stability of membranes, 73 geriatric outpatients of the Clinical Hospital of the Federal University of Uberlândia, were evaluated in a prospective, observational, cross-sectional study. Nutritional status was estimated using the Mini-Nutritional Assessment (MNA). Depression was detected using the Geriatric Depression Scale (GDS). The stability of membranes was assessed in erythrocytes against hypotonic shock by spectrophotometry and expressed by the half-point of transition (H50) of the sigmoidal curve of hemolysis. The values of MNA showed significant correlations only with age but not with blood levels of folate, cobalamin and homocysteine. The GDS scores showed significant correlations only with age but not with serum levels of folate, cobalamin and homocysteine. The values of H50 did not show significant correlations with age, scores of GDS, hematologic variables and serum levels of folate and cobalamin, but showed a significant negative correlation with the levels of homocysteine. The overall risk of malnutrition, the scores of GDS and the concentrations of homocysteine increased with age, but showed no relationship with serum levels of folate and/or cobalamin. The stability of the erythrocyte membrane showed no relationship with age or with haematological variables, but increased with increased levels of homocysteine. Possible implications and the reasons for the association between the stability of membranes and hyper-homocysteinemia are discussed.